2014
DOI: 10.1371/journal.pntd.0003148
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Free-living Amoebae as a Reservoir for Mycobacterium ulcerans

Abstract: BackgroundThe reservoir and mode of transmission of Mycobacterium ulcerans, the causative agent of Buruli ulcer, still remain a mystery. It has been suggested that M. ulcerans persists with difficulty as a free-living organism due to its natural fragility and inability to withstand exposure to direct sunlight, and thus probably persists within a protective host environment.Methodology/Principal FindingsWe investigated the role of free-living amoebae as a reservoir of M. ulcerans by screening the bacterium in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 44 publications
1
28
0
2
Order By: Relevance
“…In their protozoan hosts, "hidden" mycobacteria might find easier opportunities to infect vertebrate end hosts, multiplying within protozoans to escape immune reactions (480). This ability to persist within amoebae has been widely documented (481)(482)(483). The internalization of infectious agents inside other parasites represents an evolutionary strategy for survival that may sometimes enhance pathogenesis or transmissibility (480).…”
Section: Interactions Between Actinobacteria and Invertebratesmentioning
confidence: 99%
“…In their protozoan hosts, "hidden" mycobacteria might find easier opportunities to infect vertebrate end hosts, multiplying within protozoans to escape immune reactions (480). This ability to persist within amoebae has been widely documented (481)(482)(483). The internalization of infectious agents inside other parasites represents an evolutionary strategy for survival that may sometimes enhance pathogenesis or transmissibility (480).…”
Section: Interactions Between Actinobacteria and Invertebratesmentioning
confidence: 99%
“…Underwater detritus at a localized position of the water hole was repeatedly tested positive for M. ulcerans-specific DNA sequences over a period of more than 2 years after all local BU cases had been treated [45], suggesting that M. ulcerans has adapted to survive in a restricted niche environment. Several studies have indicated that M. ulcerans is unlikely to be free-living and may persist in the environment as a commensal, associated with another protective organism such as amoeboid protozoa or inhabitants of biofilms in stagnant water bodies [46][47][48]. Characteristic genome signatures of M. ulcerans including (1) the acquisition of foreign DNA such as pMUM, IS2404, and IS2606, (2) the proliferation of IS elements, (3) extensive gene loss through pseudogene formation, and (4) genome downsizing, provide further evidence that M. ulcerans is adapting to a new, probably relatively protected and stable ecological niche [11•, 49, 50].…”
Section: Environmental Reservoirsmentioning
confidence: 99%
“…ulcerans have been shown to survive in free living amoeba [27]. Studies by Gryseels et al [22] and Amissah et al [28] have also confirmed that M . ulcerans can survive in Acanthamoeba spps.…”
Section: Discussionmentioning
confidence: 94%